Co-creating content with children to avoid 'Uncle Swag': Strategies for producing public service television drama for tweens and teens at the Danish children's channel DR Ultra. (June 2021) - Redvall, Eva Novrup; Christensen, Katrine Bouschinger
This article explores the strategies for fictional content of the Danish children's channel DR Ultra through a qualitative case study of the production framework behind its successful series Klassen (2016–now). Building on studies of television production and theories of co-creation, the analysis investigates the use of co-creative initiatives during the development and writing as well as the production of programmes. The analysis highlights the value of involving children more closely in content targeting them, not only to ensure that what is told and how it is told is relevant and appealing, but also to create a sense of participation and co-creation.